The Relationship between the Supervisor’s Transformational Leadership as Perceived by the Employees with Job Performance and Job Satisfaction of Phathong Thungsong Co, Ltd. and Phathong 24 Co., Ltd. - Sapsong, Pemika (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The objectives of the research were 1) to study level of the supervisor’s transformational leadership, job performance and job satisfaction and 2) to study the relationship between the supervisor’s transformational leadership with job performance and job satisfaction. The samples used in this study were composed of 215 employees from the two companies. The data collected by the questionnaires. The data analysis was based on arithmetic means, standard deviation, hypothesis testing used correlation coefficient and multiple correlation coefficient. The findings found that the supervisor’s transformational leadership as a whole was in moderate level. When considering on a case respectively, idealized influence, individualized consideration, inspirational motivation and intellectual stimulation, job performance and job satisfaction as a whole was in high level. And the supervisor’s transformational leadership as perceived by the employees had a positive relationship with job performance and job satisfaction of Phathong Thungsong Co., Ltd. and Phathong 24 Co., Ltd. at 0.01 statistically significant level.